Exploring the diagnosis delay and ALS functional impairment at diagnosis as relevant criteria for clinical trial enrolment*. Issue 7 (2nd October 2017) - Hamidou, Bello; Marin, Benoit; Lautrette, Geraldine; Nicol, Marie; Camu, William; Corcia, Philippe; Arnes-Bes, Marie-Christine; Tranchant, Christine; Clavelou, Pierre; Hannequin, Didier; Maurice, Giroud; Beauvais, Katell; et al.
Abstract: Objectives were : i) to describe the phenotypic heterogeneity of incident amyotrophic lateral sclerosis (ALS) patients diagnosed in 2012 in French ALS centres; ii) to look at the associations between ALSFRS-R score and ALSFRS-R slope (ΔFS) at time of diagnosis with diagnosis delay, ALS phenotypes and Airlie House diagnosis criteria (AHDC); iii) to describe the rate of progression on ΔFS, according to diagnosis delay. Methods : Incident ALS cases diagnosed in French ALS centres were included. The rate of progression was evaluated as follows: ΔFS = (48 – ALSFRS-R at time of diagnosis)/duration from onset to diagnosis (months). Fast and slow progressors were defined by ΔFS >1 and <0.5, respectively. Results : At time of diagnosis, 476 patients were classified into eight phenotypes: bulbar (33.0%), spinal lumbar (28.2%), spinal cervical (23.1%), flail leg (4.4%), ALS/FTD (4.2%), possible flail arm (4.0%), respiratory (2.1%), dropped-head (1.0%). Median ΔFS ( n = 358/476) was 1.0 [0.5–2.0]. ΔFS was associated with AHDC ( p = 0.009), but not with clinical phenotype ( p = 0.902). Stratification on diagnosis delay (<12 months or ≥18 months) allowed to differentiate fast progressors from slow progressors. Conclusion : At time of inclusion in therapeutic trial closed to diagnosis, ΔFS or diagnosis delay may discriminate the rate of progression.